Mole rats act as ecosystem engineers within a biodiversity hotspot, the Cape Fynbos. (13th August 2012) - Hagenah, N.; Bennett, N. C.; Kitchener, Andrew
Abstract Through their burrowing and foraging activities, subterranean rodents disturb large amounts of soil. As a result, they may modify physical and chemical soil properties and thus change the productivity, structure and dynamics of plant communities. To date, research on the ecological importance of fossorial mammals has focused predominantly on subterranean rodents in North and South America, Europe and Asia. Surprisingly, despite the potential of them filling a similar ecological niche, very few studies have focused on the impacts of mole rats (Bathyergidae) in Africa. To determine how mole rats modulate their environment, we examined the soil and vegetation properties of mole rat‐modified habitats in the Cape Floristic Region, South Africa. We predicted that excavation would result in mound soils having higher nutrient levels, more uniform soil particle profiles and lower compactness compared with undisturbed soils. Furthermore, we expected their digging and foraging activities would change plant species composition and increase plant productivity and diversity. As predicted, we found that soils disturbed by mole rats had higher nutrient levels and lower compactness compared with undisturbed soils, and an altered plant species composition. However, in contrast to our predictions, mounds had a finer particle size profile, and mole rat burrowing and foraging lowered the overall aboveground plant biomass. Most importantly, the presence of mole rats enhanced plant species richness. However, as disturbance increased plant species richness declined. Our findings suggest that in Africa, mole rats fulfil the same ecological niche as their ecological cognates in other ecosystems and thus ultimately act as ecosystem engineers.